The ghost fields - Griffiths, Elly (Griffiths, Elly. Ruth Galloway mystery., 2015)
"The macabre discovery of a downed WWII plane with the pilot's skeleton still inside leads Ruth and DCI Nelson to uncover a wealthy family's secrets in the seventh Ruth Galloway mystery" --